Continuation of breastfeeding after surgical removal of AQUALIFTⓇ due to mastitis: A case report - Kayoko Uno; Yushi Suzuki; Yukie Nakamura; Kazuo Kishi (JPRAS Open)
Several complications have been reported following copolyamide filler injections for breast augmentation leading many countries to issue warnings regarding the use of nonabsorbable fillers. While previous reports have described breast complications necessitating surgical intervention after filler injections, none have explicitly documented the continuation of postoperative breastfeeding. Here, we report a rare case in which a woman with a history of breast augmentation using AQUALIFTⓇ developed mastitis following childbirth and the initiation of breastfeeding. Despite requiring surgical removal of the AQUALIFTⓇ, she successfully continued breastfeeding owing to a strong desire and commitment to regular milk expression throughout the perioperative period.Nevertheless, the carcinogenicity and toxicity of copolyamide, its presence in breast milk, and its effects on breastfed infants remain unclear. While various authorities have issued warnings concerning the use of fillers for breast augmentation, a significant number of women have already undergone this procedure. As these women reach childbearing age, further research is required to evaluate the safety of breastfeeding after filler-based augmentation.